Households Forming Inflation Expectations: Who Are the 'Active' and 'Passive' Learners? - Joshy Easaw; Roberto Golinelli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2009)
Recent research has established that households learn from professional forecasters as they form their inflation expectations. Professionals forecasts are transmitted, or 'absorbed', throughout the population slowly but eventually. This provides the microfoundations for 'sticky information expectations'. The present paper considers whether absorption rates take place heterogeneously amongst households. We consider whether various segments of the population absorb the professional's forecasts at different rates. Using a unique survey-based dataset covering various segments of the UK population we identify 'active' and 'passive' learners in the population. 'Active' and 'passive' learners are identified and distinguished by their respective absorption rates. The present analyses also consider whether these absorption rates are non-linear.
Keywords: 330